2019
DOI: 10.5194/bg-16-3283-2019
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic nutrients dominate melting surface ice of the Dark Zone (Greenland Ice Sheet)

Abstract: Abstract. Glaciers and ice sheets host abundant and dynamic communities of microorganisms on the ice surface (supraglacial environments). Recently, it has been shown that Streptophyte glacier algae blooming on the surface ice of the south-western coast of the Greenland Ice Sheet are a significant contributor to the 15-year marked decrease in albedo. Currently, little is known about the constraints, such as nutrient availability, on this large-scale algal bloom. In this study, we investigate the relative abunda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 62 publications
9
44
0
Order By: Relevance
“…Second, DIP may not be as limiting in supraglacial environments as previously believed (Hodson et al, 2004;Stibal et al, 2008Stibal et al, , 2009, considering that DIN was consistently consumed during the present study when concentrations were artificially elevated. Such trends have also been reported in recent studies concerning both snow pack and surface ice environments, which suggested DIN to be in higher demand than DIP (Larose et al, 2013a;Holland et al, 2019). Overall, there is a clear response by the microbial community to all nutrient additions over the course of just 5-weeks in a cold, dark snow pack, indicating that the 24-h darkness and subfreezing temperatures of the polar winter may not be as limiting as previously thought.…”
Section: Varied Heterotrophic Community Response To Dissolved Nutriensupporting
confidence: 81%
“…Second, DIP may not be as limiting in supraglacial environments as previously believed (Hodson et al, 2004;Stibal et al, 2008Stibal et al, , 2009, considering that DIN was consistently consumed during the present study when concentrations were artificially elevated. Such trends have also been reported in recent studies concerning both snow pack and surface ice environments, which suggested DIN to be in higher demand than DIP (Larose et al, 2013a;Holland et al, 2019). Overall, there is a clear response by the microbial community to all nutrient additions over the course of just 5-weeks in a cold, dark snow pack, indicating that the 24-h darkness and subfreezing temperatures of the polar winter may not be as limiting as previously thought.…”
Section: Varied Heterotrophic Community Response To Dissolved Nutriensupporting
confidence: 81%
“…Figure 2c also shows that the cryoconite and ice samples are distributed along two parallel directions. This suggests that a factor not investigated in this study (e. g. irradiation, pH, total organic carbon, nutrients concentration) may describe part of the unexplained variance of the algal community 51 . Given the complexity of the supraglacial environment, even the relatively low explained variance (i.e.…”
Section: Resultsmentioning
confidence: 89%
“…On the Greenland Ice Sheet, algal cell abundance, which ranged from 90 cells · mL −1 to 0.98 × 10 4 cells · mL −1 , increased significantly with the amount of visible impurities seen on the ice surface (Holland et al. ). Correlations between average algal cell counts and DON and DOC surface ice concentrations were significant.…”
Section: Diversity and Community Structurementioning
confidence: 99%